Frontier rule and conflict - Muhammad Adeel Malik; Rinchan Ali Mirza; Faiz Ur Rehman (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2023)
We examine whether frontier rule, which disallows frontier residents from a recourse to formal institutions of conflict management and disproportionately empowers tribal elites, provides a more fragile basis for maintaining social order in the face of shocks. Combining a historical border separating frontier from non-frontier regions in north-western Pakistan with 10km-by10km grid cell-level data on conflict in a spatial regression discontinuity design framework, we show that areas that historically fell under frontier rule experienced significantly higher violence against the state after 9/11. We argue that the 9/11 tragedy represented a shock to grievances against the state which, in the absence of formal avenues of conflict management, led to a sharp surge in attacks against state targets in frontier areas. We show that the surge in 'sovereigntycontesting' forms of violence in these regions was partly carried out through the systematic assassination of tribal elites who were the main pillar of frontier rule that guaranteed social order. In our empirical analysis we rule out several important competing explanations behind the post9/11 rise in violence in frontier areas, including the possibility of conflict spilling over from Afghanistan, income shocks (proxied by military operations), and drone attacks.
Keywords: D02; D74; N45; P48; 330; institutions; historical frontiers; conflict